Screen Printed-Carbon Electrode Modifikasi Bismut untuk Analisis Kadmium dengan Voltametri Siklik - Novianti Novianti; R V Manurung; Arifin Arifin (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Cadmium (Cd) is a heavy metal that has high toxicity. Cadmium levels need to be considered in an environment that can accumulate and can poison all biotic components. In this research measurements of cadmium metal using bismuth-modified carbon screen electrode used cyclic voltammetry method. The parameters considered are the resolution of the comparative electrodes and the voltage produced from variations in cadmium concentration. The test results prove the stability of three sensors each at a voltage of 3.3 - 4.6 mV, 9.3-11.4 mV, and 27.4 - 29.8 mV. While the results of the cyclic voltammetry characterization test vary depending on the concentration of cadmium. Concentrations of 0.5-100 ng / mL produce an oxidation peak at a current of 2.03 x 10-5 - 5.00 x 10-5 A. These results show a directly proportional relationship between the cadmium concentration and the resulting current.